Profit analysis of a computer system with preventive maintenance and priority subject to maximum operation and repair times - Kumar, Ashish; Saini, Monika (Iran Journal of Computer Science (Online), 2018)
The aim of the present study is to carry out the profit analysis of a computer system by considering the concept of priority to preventive maintenance over different hardware and software repair activities. For this purpose, three stochastic models have been developed under different priority policies. A single repair facility is available to perform all repair activities. The hardware unit undergoes replacement after a pre-specific maximum repair time. The repairman performs the preventive maintenance of the whole system after a pre-fixed maximum operation time. All time-dependent failure rates follow exponential distribution, while the repair rates follow arbitrary distribution. Switch devices, repairs and preventive maintenance are perfect. All random variables are statistically independent. Semi-Markov process and regenerative point technique were used to derive the necessary system effectiveness measure to evaluate the profit function of all the three models. To highlight the importance of the study, graphs for profit difference between models have been depicted for a particular set of values of various parameters with respect to preventive maintenance.